Discourse on Creating a Special Environmental Court in Indonesia to Resolve Environmental Disputes - Suwari Akhmaddhian (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2020)
The purpose of this study is to determine the regulation of laws and regulations regarding environmental justice in Indonesia and how the concept of building environmental justice in the justice system in Indonesia. This research can be useful both practically and theoretically, practically. The research method used by researchers is the evaluative analysis method, which is a method of gathering and presenting data obtained to analyze the actual situation and then rational analysis is carried out based on juridical references through library research. The results of the research Regulations on the environment are already available namely Law Number 32 of 2009 concerning Environmental Protection and Management and building an environmental justice system starting from improving human resources namely the Supreme Court by consistently educating and training judges with knowledge of aspects of environmental law life that will later handle environmental cases; The Supreme Court makes a special assembly that handles environmental cases; The Supreme Court creates a special chamber that is integrated with the general court that handles environmental cases; The government is amending the 1945 Constitution specifically Article 24 by adding the judicial environment to the environmental court. The conclusion of the legislation is already available and must be used as well as possible and amend the laws and regulations so that bias can be created specifically for environmental justice. Keywords: Building; Environmental; Justice System.